Outcomes in stage IIA versus stage IIB/III in the PALLAS trial [ABCSG-42/AFT-05/PrE0109/BIG-14-13]) - A. DeMichele; A. C. Dueck; D. Hlauschek; M. Martin; H. Burstein; G. Pfeiler; N. Zdenkowski; A. Wolff; M. Bellet-Ezquerra; E. Winer; M. Balic; K. Miller; et al. (Breast Cancer Research)
Abstract Background The PALLAS trial investigated the addition of palbociclib to standard adjuvant endocrine therapy to reduce breast cancer recurrence. This pre-specified analysis was conducted to determine whether adjuvant palbociclib benefited patients diagnosed with lower risk stage IIA disease compared to those with higher stage disease. Methods PALLAS was an international, multicenter, randomized, open-label, phase III trial, representing a public–private partnership between Pfizer, the Austrian Breast Cancer Study Group, and the U.S. ALLIANCE Foundation. Patients diagnosed with stage II–III, hormone-receptor-positive, HER2/neu negative breast cancer within 12 months of diagnosis had completed all definitive therapy aside from endocrine therapy (started within 6 months prior to study entry) were eligible. All patients were required to submit a formalin-fixed paraffin-embedded (FFPE) tumor block. Patients were randomly assigned 1:1 to receive standard adjuvant endocrine therapy (of physicians’ choice) for at least 5 years with or without 2 years of palbociclib, administered orally at a starting dose of 125 mg daily, given for 21 days followed by a 7-day break. Results A total of 5,796 patients with HR + /HER2- early breast cancer (including 1,010 with stage IIA) were enrolled. Median follow-up was 50 months for stage IIA patients and 43.1 months overall. In the stage IIA cohort, 4-year iDFS in the palbociclib arm was 92.9% versus 92.1% for ET alone (HR 0.75, 95%CI 0.48–1.19, p = 0.23). There was no differential benefit by histologic grade, chemotherapy receipt, age, or anatomic/clinical risk. Additionally, no benefit to palbociclib was seen in this cohort in invasive breast cancer-free survival (iBCFS), locoregional relapse-free survival (LRFS), distant relapse-free survival (DRFS), or overall survival (OS). For the stage IIB/III patients, 4-year iDFS was 85.3% for palbociclib + ET versus 83.6% for ET alone (HR 0.91, 95% CI 0.77–1.07, p = 0.24). Conclusions and relevance While there were substantial differences in outcome for stage IIA versus IIB/III patients at 4 years of follow-up, the addition of 2 years of palbociclib did not improve outcomes for patients, regardless of stage. Trial Registration ClinicalTrials.gov number NCT02513394 Registered 30 Jul 2015.